Functional Connectivity of the Human Red Nucleus in the Brain Resting State at 3T - Nioche, C.; Cabanis, E.A.; Habas, C. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Previous structural data obtained with diffusion tensor imaging axonal tracking have demonstrated possible in vivo connections between the human red nucleus (RN) and the sensorimotor and associative cortical areas. However, tractographic reconstructions can include false trajectories because of, for instance, the low spatial resolution of diffusion images or the inability to precisely detect fiber crossings. The rubral network was therefore reassessed by functional connectivity during the brain resting state. Because the RN is located very close to the substantia nigra (SN), the nigral network was also studied to ensure that these 2 circuits were correctly dissociated.MATERIALS AND METHODS: Data from 14 right-handed healthy volunteers were acquired at rest and analyzed by region-of-interest (ROI)–based functional connectivity. The blood oxygen level–dependent (BOLD) signal intensity fluctuations of separate ROIs located in the RN and SN were successively used to identify significant temporal correlations with BOLD signal intensity fluctuations of other brain regions.RESULTS: Low-frequency BOLD signal intensity of the RN correlated with signal intensity fluctuations in the cerebellum; mesencephalon; SN; hypothalamus; pallidum; thalamus; insula; claustrum; posterior hippocampus; precuneus; and occipital, prefrontal, and fronto-opercular cortices. Despite some cortical and subcortical overlaps with nigral connectivity, this rubral network was clearly distinct from the nigral network, which showed a strong correlation with the striatum; cerebellar vermis; and more widespread frontal, prefrontal, and orbitofrontal cortical areas.CONCLUSIONS: During the brain resting state, the human RN participates in cognitive circuits related to salience and executive control, and that may partly represent a subclass of its structural connectivity as revealed by tractography.